The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fnmol.2022.801757
|View full text |Cite
|
Sign up to set email alerts
|

Metabotropic Glutamate Receptor 5 Antagonism Reduces Pathology and Differentially Improves Symptoms in Male and Female Heterozygous zQ175 Huntington’s Mice

Abstract: Huntington’s disease (HD) is an inherited autosomal dominant neurodegenerative disorder that leads to progressive motor and cognitive impairment. There are currently no available disease modifying treatments for HD patients. We have previously shown that pharmacological blockade of metabotropic glutamate receptor 5 (mGluR5) signaling rescues motor deficits, improves cognitive impairments and mitigates HD neuropathology in male zQ175 HD mice. Mounting evidence indicates that sex may influence HD progression and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“… 86 , 87 Further, activation of upstream complement cascade components as well as aberrant mGlu 5 R signaling have been identified as central to the pathology of Huntington’s disease, Parkinson’s disease, and multiple sclerosis. 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 Therefore, it will be critical for future studies to elucidate whether the pathological mGlu 5 R-NMDAR-C5aR1 signaling axis identified in our study underlies synapse deterioration in multiple brain disorders.…”
Section: Discussionmentioning
confidence: 96%
“… 86 , 87 Further, activation of upstream complement cascade components as well as aberrant mGlu 5 R signaling have been identified as central to the pathology of Huntington’s disease, Parkinson’s disease, and multiple sclerosis. 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 Therefore, it will be critical for future studies to elucidate whether the pathological mGlu 5 R-NMDAR-C5aR1 signaling axis identified in our study underlies synapse deterioration in multiple brain disorders.…”
Section: Discussionmentioning
confidence: 96%
“…Further, studies from in vitro and mouse models of these diseases have demonstrated the necessity of C3 and/or C5 for their pathology (Woodruff, et al, 2008; McGeer, Lee, & McGeer, 2017; Wang, Lee, Lee, Woodruff, & Noakes, 2017; Hammond, et al, 2020; Bourel, et al, 2021; Chen, Hu, Ding, Du, & Hu, 2021; Gregersen, et al, 2021; Lopez-Sanchez, et al, 2022). Interestingly, mGlu 5 R has separately been identified as an emerging therapeutic target in these complement-associated neurodegenerative diseases (Geurts, et al, 2003; Abd-Elrahman, et al, 2017; Bonifacino, et al, 2017; Doria, et al, 2018; Bonifacino, et al, 2019; Farmer, et al, 2020; Su, Wang, Han, & Shen, 2021; Zhang, et al, 2021; Azam, et al, 2022; Li, Colson, Abd-Elrahman, & Ferguson, 2022). We therefore speculate that the mGlu 5 R-NMDAR-C3aR/C5aR signaling axis identified in our study may be a common feature of many brain disorders.…”
Section: Discussionmentioning
confidence: 99%
“…As in AD, the effects of mGlu 5 antagonism on HD pathology have been studied predominantly in male HD mice. Recent work compared the response of male and female zQ 175 mice to chronic treatment with CTEP ( Li et al, 2022 ). This study showed that improvements in motor and cognitive skills differed between the sexes.…”
Section: Huntington’s Diseasementioning
confidence: 99%